Tax competition, tax coordination and tax harmonization: The effects of EMU - Bernd Genser; Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
There is little doubt that the step towards a monetary union in Europe will increase both the distortionary effects of existing differences in national tax systems and the intensity of tax competition for internationally mobile commodity and factor tax bases. This paper discusses selected issues of commodity and capital tax coordination that are likely to be affected by monetary unification. Starting from the distortive present scheme of value-added taxation in Europe we first analyze the effects of a switch to a general origin-based VAT as a way to maintain national tax rate autonomy over this important tax base. While an origin-based VAT would neither distort trade flows - both within the EU and with third countries - nor investment decisions in the long run, its short-run effects are likely to be severe in the absence of exchange rate flexibility. In the field of capital taxation the focus switches to the feasibility of regional harmonization measures when there is no cooperation with the rest of the world. We argue that in a monetary union the mobility costs of capital will be significantly lower within the EU as compared to outside investments. This provides an efficiency argument for minimum source taxes on both interest income and corporate profits even if cooperation with third countries is infeasible.
Keywords: 330